Work–Study Conflict and Academic Burnout among Gig-Economy Students: Evidence from Online Motorcycle Taxi Drivers - Yovhi Maulana Putra; Onny Fransinata Anggara (Journal of Educational Management Research, 2026)
This study aims to investigate the relationship between work–study conflict and academic burnout among university students working as online motorcycle taxi drivers. The increasing participation of students in the gig economy presents new challenges in balancing academic responsibilities and work demands. Persistent role pressure arising from simultaneous academic and occupational obligations may lead to psychological strain and academic exhaustion. A quantitative correlational design was employed involving 117 working students selected through purposive sampling. Data were collected using a work–study conflict scale adapted from Markel and Frone and the Maslach Burnout Inventory–Student Survey (MBI-SS). Descriptive analysis indicated moderate levels of work–study conflict and academic burnout among respondents. Assumption testing confirmed data normality, allowing the use of parametric analysis. Pearson’s correlation analysis revealed a significant positive relationship between work–study conflict and academic burnout (r = 0.565; p < 0.001). This finding suggests that greater conflict between work and academic roles is associated with increased academic exhaustion, reduced learning engagement, and lower perceived academic competence. The results emphasise the importance of role management in supporting students’ academic well-being. This study provides empirical evidence from gig-economy student workers and recommends developing flexible academic policies and institutional support systems to reduce academic burnout.